Comparative Analysis of Income Before and After Using QRIS at the Bintang Mawar Ayam Pedas Depot in Balikpapan - Agustin, Kety Lulu; Apriani, Endang Sri (MEC-J (Management and Economics Journal), 2023)
Based on Bank Indonesia Regulation No.21/18/2019 concerning the implementation of the international QRIS standard for payment, starting January 1 2020 Bank Indonesia requires all non-cash payment service providers to switch to the QRIS (Quick Response Code Indonesian Standard) system. This requires UMKMs to provide QRIS as a means of payment to make transactions easier. This research aims to find out and analyze the comparison of income at the Bintang Mawar Ayam Pedas Depot before and after using QRIS. Data collection techniques include interviews and documentation. The collected data was then analyzed using descriptive data, normality test, and partial test (t-test) using SPSS 26.0. The results of the t test calculation show a sig value. amounting to 0.006 0.05, so it can be concluded that there is effectiveness of QRIS to increase income at the Bintang Mawar Ayam Pedas Depot, the average increase per month at the Bintang Mawar Ayam Pedas Depot is IDR. 5,522,111.